Domestic legal pluralism and the International Criminal Court : the case of Shari'a law in Nigeria - Yang, Justin Su-Wan (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explores how the unique historical development of Islamic Shari'a criminal law alongside English common law in northern Nigeria has created a hybridised criminal legal system through a pluralist dynamic of mutual accommodation. It studies how this system may potentially be accommodated by the International Criminal Court. The work examines how this could be accommodated through the current understanding and operation of complementarity, and that it could ultimately prove to be preferable in encouraging the Shari'a courts to exercise criminal justice over the radical insurgents in northern Nigeria. These courts would have the unprecedented ability to combine binding adjudicative judgments together with religious interpretation and guidance, which can directly combat the predominantly unchallenged domain of ideology by extremist actors. It is submitted that these pluralist perspectives are timely and welcome, given the undeniably Western European foundations of modern International Criminal Law. In exploring such potential avenues, our shared understanding of modern international criminal justice is widened to necessarily include other stakeholders beyond its Western founders. It is the aim and hope that such interactions and engagements with non-Western traditions and cultures will lead to a greater shared ownership of the international criminal justice project, which will only strengthen the global fight against impunity. The book will be essential reading for academics, researchers and policy-makers working in the areas of International Criminal Law, Legal Pluralism, Islamic Shari'a Law, Nigeria, and religiously-inspired violence"--
Pluralism in international criminal law -- Legal pluralism and Shari'a law -- History of legal pluralism in Nigeria -- Boko Haram and Shari'a violence in Nigeria -- The International Criminal Court in Nigeria.
OCLC-licensed vendor bibliographic record.
Keywords: Boko Haram; International Criminal Court; Legal polycentricity -- Nigeria; Islamic law -- Nigeria; International and municipal law -- Nigeria; International criminal courts -- Nigeria; Criminal justice, Administration of -- Nigeria; Complementarity (International law); International criminal law; LAW / General; LAW / Courts; LAW / Criminal Law / General